The Level of Community Political Participation related to the Elections of the Regent and Deputyregent and Empty Boxes in the Simular Elections in 2024 - Hasnawi Haris; Nurharsya Khaer Hanafie; Muh. Said; Fatimah Hidayahni Amin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2022)
Direct regional head elections can be said to be one of the real forms of implementing regional autonomy, where the people can directly elect the leaders they want directly. This study tries to describe how the level of community political participation is related to the election of the Regent and Deputy Regent as well as the empty box in holding the simultaneous local elections in 2024. This study tries to describe the level of political participation of the community in a substantial and procedural manner through a review of normative literature studies and immediately goes down to see how the residents' enthusiasm for the 2024 simultaneous regional elections and interviewed several residents regarding how they are prepared to face the simultaneous regional elections in the future. It turned out that the formal procedural implementation that went well was not in line with the substantive democracy to be achieved. Democracy will be based on the principle of equality in the sense that every human being is equal; therefore there is no specialization of any particular group or assumption that one is more honorable than another. Keywords: Simultaneous Pilkada, Empty Column, Voter Participation